Performance Testing and Research of a C0 Water-Repellent Treatment for PFAS-Free Textile Applications - Knutsson,Ninni; Dunder,Erica (2026)
This study looked at a fluorocarbon-free water-repellent treatment on different types of polyester textiles in order to test the durability of the treatment in simulated wear-and-tear tests in collaboration with Thule Group. This research was being done in order to gain a deeper understanding in the strengths and limitations of the C0 Water-Repellent (C0WR) treatment on polyester textiles. The study was divided into two parts with the first one being experimental tests of the fabrics. The second part was a literature study, focusing on researching alternative methods to test hydrophobicity, as well as research different alternative water-repellent chemistries. Four different polyester fabrics was used in this study, each with and without C0WR. The different fabrics were comprised of different yarns such as Fully Drawn Yarn (FDY), Drawn Textured Yarn (DTY) and Air Textured Yarn (ATY). These fabrics were tested in three environments simulating wear and tear, the Martindale machine simulating abrasion, washing machine simulating household washing and an Artificial Weathering (AW) chamber simulating the fabrics being exposed to UV-light and moisture. After AW, the samples were also tested in the Martindale machine. Before and after all of the test were conducted, the samples' hydrophobicity were tested with the help of the Water Spray Test. The results from the experimental study showed that there was a decrease in hydrophobicity after each of the tests for all of the four different fabrics. The fabric that was noted to perform slightly better in comparison was the FDY x DTY fabric. The literary study presented another method in testing hydrophobicity using Contact Angle (CA) measurements which is a useful test that can measure how well a fabric resists wetting. In the literature, several different chemistries were presented as alternative solutions to a water-repellent treatment. These were paraffin based, stearic acid based, dendrimer based, nanoparticle based and OrganoClick, a company using bio-based surfactants in an emulsion to create its water-repellent. All of these chemistries could have the potential to be good alternatives to fluorocarbon-based treatments. The research showed that all mentioned chemistries exhibited good hydrophobicity, and there were even instances of exhibiting superhydrophobicity.
Keywords: C0 Water-Repellent; C0WR; PFAS-Free Water-Repellent Treatment; Fluorocarbon-Free Water-Repellent Treatment; Polyester Textile; Martindale; Artificial Weathering; Water Spray Test; Scanning Electron Microscope; SEM; Contact Angle; CA; polymer technology